Dissolving royal marriages a documentary history 860-1600 - D'Avray, D.L. (Cambridge, United Kingdom Cambridge University Press, 2014)
In a chronological and geographical study of royal divorce cases from the MIddle Ages through to the reformation, D'Avary offers a truly comparative perspective on elite divorce, tracing its evolution overtime, and providing original translations of documents which illuminate the canon law arguments on which the cases were built.
Includes bibliographical references (p. 300-306)
Keywords: Marriage of royalty and nobility -- History; Royal houses -- Europe -- History; Divorce -- Europe -- History; Europe -- Kings and rules; Europe -- Politics and government